On the Relation between Discounting of Climate Change and Edgeworth-Pareto Substitutability - Tomas Kögel (Economics: The Open-Access, Open-Assessment E-Journal, 2011)
To justify substantial carbon emission reductions, recent literature on cost-benefit analysis of climate change suggests discounting environmental quality at a lower discount rate than the standard consumption discount rate. Recent literature also shows that a theoretical foundation for such a lower environmental discount rate requires rising willingness-to-pay for environmental quality (WTP). A widely believed better alternative is however to adjust instead future environmental benefits for rising WTP and to discount those benefits at the consumption discount rate. According to this latter approach, rising WTP is usually assumed not to change the consumption discount rate itself. Assuming environmental resource scarcity, the present paper shows that an unchanged consumption discount rate is however, by and large, only an appropriate assumption in the knife-edge case in which environmental quality and goods consumption are neither substitutes nor complements in the Edgeworth-Pareto sense (substitutes, respectively, complements in the Edgeworth-Pareto sense implies the marginal utility of goods consumption to be decreasing, respectively, increasing in environmental quality).
Keywords: H43; Q51; Q54; 330; Discounting; cost-benefit analysis; climate change; Klimaschutz; Kosten-Nutzen-Analyse; Umweltökonomik; Soziale Diskontrate; Theorie